Meninjau Perubahan Sosial Kultur Masyarakat Terdampak Lumpur Sidoarjo Setelah 2 Dekade dengan Wawancara Elisitasi Foto - Dwi Oktavian Widyatama; Aryo Bayu Wibisono; Masnuna Masnuna (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The Sidoarjo mudflow eruption in Porong, Sidoarjo, that have been flowing since 2006 has caused long-term impacts on the affected communities. the impact in question are people losing their job, change in social interaction and culture that are applied everyday by the communities. This study aims to examine the socio-cultural changes that are experienced by the community two decades after the disaster. The research employs a qualitative approach using photo elicitation through five photographs that are taken in the affected area map as prompts for resource person to reflect and recount their experience that they undergo, then will be conducted semi-structured interviews. The findings indicate a transformation of the physical landscape, which has led to shifts in social structures, the weakening of communal bonds, and changes in collective identity. Memories of the former homeland and the continuation of annual commemorative practices demonstrate that the disaster remains embedded in the community’s social life. These findings affirm that the impacts of the disaster are not merely physical, but also social and cultural in between communities in the long term and continuosly happening.